Palliative systemic therapy for advanced non-small cell lung cancer: Investigating disparities between patients who are treated versus those who are not. (July 2016) - Brule, Stephanie Y.; Al-Baimani, Khalid; Jonker, Hannah; Zhang, Tinghua; Nicholas, Garth; Goss, Glenwood; Laurie, Scott A.; Wheatley-Price, Paul
Highlights: Nearly half of all patients with advanced NSCLC did not receive any systemic therapy. The most common reason for lack of treatment was due to a poor performance status. Untreated patients had poorer prognostic features and shorter overall survival. We must allocate research equitably to improve outcomes in the untreated and unfit. Abstract: Background: Palliative systemic therapy (ST) in advanced non-small cell lung cancer (NSCLC) is associated with improved overall survival (OS) and quality of life, yet many patients remain untreated. We explored differences between patients who did and did not receive palliative ST in order to gain evidence to support and advocate for the untreated. Methods: We performed a retrospective analysis of newly diagnosed patients with advanced, incurable NSCLC seen as outpatients at our institution between 2009 and 2012. Demographics, treatment, and survival data were collected. Results: 528 patients were seen: 291 (55%) received palliative ST, while 237 (45%) received none. Demographics were as follows: Median age 67, 55% male, 50% ECOG performance status (PS) 0–1, 48% with weight loss. Untreated patients were older (median 71 vs. 64, p < 0.01), less fit (PS 0–1 in 27% vs. 69%, p < 0.01), and more likely to have lost weight (57% vs. 41%, p < 0.01). Reasons for no treatment included poor PS (67%) and patient choice (23%). Median OS was shorter amongst untreated patients (3.9 vs. 10.7 months, HR 1.80 [95% CI 1.4–2.3], p < 0.01). In multivariate analysis, not receiving ST was associated with shorter OS. Conclusion: Unsurprisingly, untreated patients had poorer prognostic features and worse OS. However, it is concerning that, despite being seen in an active academic center, nearly half of all referred patients with advanced NSCLC received no anti-cancer treatment. Current research primarily seeks to improve outcomes in treated patients with good PS. This review suggests that this is an inappropriate allocation of research effort. Our research should be more equitably split between good and poor performance patient groups if we are to improve the survival of all patients with advanced NSCLC. Potential strategies include more rapid diagnosis prior to functional decline, and the development of therapies effective and tolerated in a sicker population.